New genera and species of bamboo leafhopper tribes Mukariini and Punctulini (Hemiptera: Cicadellidae: Deltocephalinae) in Thailand - Viraktamath, C.a.; Dietrich, C.h.; Yeshwanth, H.m. (Zootaxa, 2026)
Leafhoppers of the tribes Mukariini and Punctulini of the subfamily Deltocephalinae collected using Malaise traps in National Parks of Thailand were studied. This resulted in the discovery of several new genera and species of these two tribes. New taxa of Mukriini discovered include Advita gen. nov. with its type species A. maculata sp. nov., Flatfronta thaiensis sp. nov., Mohunia qudripunctata sp. nov., Myittana (Myittana) fuscovenosa sp. nov., Myittana (Savasa) alata sp. nov., M. (S.) duvidha sp. nov., M. (S.) tuberculata sp. nov., M. (S.) unica sp. nov., Scaphotettix chaturdanta sp. nov., Setubandha gen. nov., with its type species S. attenuata sp. nov. and Thaimukaria gen. nov. with its type species T. spinosa sp. nov.. New taxa recognised in the tribe Punctulini include Clavoreticula gen. nov. with its type species Clavoreticula (Clavoreticula) biprocessa sp. nov., C. (C.) triprocessa sp. nov., Clavoreticula (Radana) subgen. nov. with its type species C. (R.) circinantis sp. nov., Cornutipyga gen. nov. with its type species C. ventriprocessa sp. nov., Thaipunctulus gen. nov. with its type species T. bidentis sp. nov.. The following species of Mukariini are new records for Thailand: Myittana (Benglebra) alami (Mahmood & Ahmed), Myittana (Myittana) modesta Distant and Scaphotettix striatus Dai & Zhang. All the taxa dealt with are described and or diagnosed and illustrated. Keys to identify the world genera of Mukariini and Punculini are also provided.